The great vegan bean book : legumes, lentils, and peas galore! more than 100 delicious plant-based dishes packed with the kindest protein in town! most recipes are soy- and gluten-free! /: legumes, lentils, and peas galore! more than 100 delicious plant-based dishes packed with the kindest protein in town! most recipes are soy- and gluten-free!. (2013) - Unknown
No abstract available